Agrobacterium-mediated genetic transformation of yam (Dioscorea rotundata): an important tool for functional study of genes and crop improvement - Nyaboga, Evans; Tripathi, Jaindra N.; Manoharan, Rajesh; Tripathi, Leena (Frontiers in Plant Science, 2014)
Although genetic transformation of clonally propagated crops has been widely studied as a tool for crop improvement and as a vital part of the development of functional genomics resources, there has been no report of any existing Agrobacterium-mediated transformation of yam (Dioscorea spp.) with evidence of stable integration of T-DNA. Yam is an important crop in the tropics and subtropics providing food security and income to over 300 million people. However, yam production remains constrained by increasing levels of field and storage pests and diseases. A major constraint to the development of biotechnological approaches for yam improvement has been the lack of an efficient and robust transformation and regeneration system. In this study, we developed an Agrobacterium-mediated transformation of Dioscorea rotundata using axillary buds as explants. Two cultivars of D. rotundata were transformed using Agrobacterium tumefaciens harboring the binary vectors containing selectable marker and reporter genes. After selection with appropriate concentrations of antibiotic, shoots were developed on shoot induction and elongation medium. The elongated antibiotic-resistant shoots were subsequently rooted on medium supplemented with selection agent. Successful transformation was confirmed by PCR, Southern blot analysis and reporter genes assay. Expression of gusA gene in transgenic plants was also verified by RT-PCR analysis. Transformation efficiency varied from 9.4% to 18.2% depending on the cultivars, selectable marker genes and the Agrobacterium strain used for transformation. It took 3–4 months from Agro-infection to regeneration of complete transgenic plant. Here we report an efficient, fast and reproducible protocol for Agrobacterium-mediated transformation of D. rotundata using axillary buds as explants, which provides a useful platform for future genetic engineering studies in this economically important crop.